2020
DOI: 10.1177/0021998320981134
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube/polyetheretherketone nanocomposites: mechanical, thermal, and electrical properties

Abstract: High-temperature engineering thermoplastics are gaining growing interests as they not only provide a lightweight solution but also affect the manufacturing processes and efficiencies. Polyetheretherketone (PEEK) is a semi-crystalline one to meet such requirement, and has been widely used as the matrix for fiber-reinforced plastics and nanocomposites. Owing to their superior physical properties, carbon nanotubes (CNTs) can be introduced into PEEK matrix in order to further improve the performances. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 135 publications
0
11
0
Order By: Relevance
“…The effect of particles on crack growth can be divided into two types, one is to consume fracture energy and decelerate crack growth, another is to become stress concentration area and induce crack initiation. Figure 12A shows the enhancement mechanism of CNTs, the studies [ 34,35 ] indicated that the well dispersion CNTs increased work consumed during pullout, the CNTs with chemical graft improved bonding strength between CNTs and resin, which intensified the energy consumed during the bonds broken, thus improved the interface properties macroscopically. Figure 12B shows the pinning mechanism of nanoparticles, due to a great stiffness than resin, the path of crack propagation would deflection, which consumed fracture energy and resulted in the slowdown of crack propagation speed.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of particles on crack growth can be divided into two types, one is to consume fracture energy and decelerate crack growth, another is to become stress concentration area and induce crack initiation. Figure 12A shows the enhancement mechanism of CNTs, the studies [ 34,35 ] indicated that the well dispersion CNTs increased work consumed during pullout, the CNTs with chemical graft improved bonding strength between CNTs and resin, which intensified the energy consumed during the bonds broken, thus improved the interface properties macroscopically. Figure 12B shows the pinning mechanism of nanoparticles, due to a great stiffness than resin, the path of crack propagation would deflection, which consumed fracture energy and resulted in the slowdown of crack propagation speed.…”
Section: Resultsmentioning
confidence: 99%
“…The doped polymers are changed in the conduction properties from insulator materials to semiconductor materials. The relative carrier concentration (n) and the carrier mobility (μ) related to the conductivity ζ [7].…”
Section: ………………(1)mentioning
confidence: 99%
“…High-temperature engineering thermoplastics are gaining growing interest as they provide a lightweight solution, with outstanding properties, at high temperatures [ 1 , 2 , 3 ]. Polymers that can fulfil these requirements are grouped together as high-temperature polymers.…”
Section: Introductionmentioning
confidence: 99%